Case report: Successful and effective percutaneous closure of a deep femoral artery pseudoaneurysm using proglide device - Jiaxin, Liu; Yan, Li; Sheng, Zhang; Zhiyi, Dong; Jichang, Wang; Shaoying, Lu (Frontiers in Surgery, 2023)
A 61-year-old man developed severe swelling in the left lower extremity after interventional embolization of liver tumor. Ultrasound examination showed a pseudoaneurysm and thrombosis in the upper thigh on the left. To recognize the causes and determine the effective therapy, lower extremity arteriography was performed. The results revealed a pseudoaneurysm arised from deep femoral artery. Considering of the size of cavity and symptoms of patient, a new method was tried instead of traditional treatment using PROGLIDE device. Postoperative angiography showed a powerful blocking effect. This case study provide us a specific treatment for pseudoaneurysm, and this method provide us a new therapeutic strategy in clinical practice.